EFFECT OF COMPENSATION AND WORK CONFLICT ON COLLECTOR EMPLOYEE PERFORMANCE - Manshur, Jasmar; Hermansyah, Hermansyah (International Journal of Business and Information Technology, 2021)
This Research Was Conducted At PT. Adira Dinamika Multi Finance Tbk Pekanbaru. This Finance Is Serving Various Financial Needs, Especially Adira Kredit division. Some of the available financial services are new and used car loans, new and used motorcycle loans Some of the available financial services are new and used car purchase services, new and used motorcycle loans, Smartphone Loans And Other Electronic Goods Loans. The entire population of 38 people in this study will be used as samples with sampling methods, namely saturated sampling and census techniques. The purpose of this research is to find Effect Of Compensation And Work Conflict On Collector Employee Performance on PT. Adira Dinamika Multi Finance Tbk Pekanbaru. Types and sources of data are primary data and secondary data obtained through interviews and questionnaires. This study uses descriptive analysis with a quantitative approach as a data collection tool. The results of this study obtained an equation that is Y = 2.105 + 0.341X1 + 0.542X2, and the value of Fcount is 21.104 d> Ftable 3.27. Based on the results of the study, it can be concluded that the variables of compensation and work conflict have a positive and significant influence on the performance of collector employees at PT Adira Dinamika Multi Finance Tbk Pekanbaru.